Bulls Are More Efficient Than Steers with Similar Meat Quality - D. U. Thomson; M. E. Youngers; E. F. Schwandt; S. J. Bartle; M. Siemens; J. C. Simroth; C. D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2017)
Bull breeding soundness evaluations are often performed as a critical component of beef cow herd management to ensure that herd bulls have adequate semen quality, are physically capable of enduring the breeding season, and to determine the serving capacity per bull. Currently, there are approximately 30.3 million beef cows and 2.1 million bulls in the U.S. Depending on the breeding soundness evaluation failure rate, there are likely several hundred thousand bulls which will enter the beef market annually and a portion will be young bulls with the potential to be fed and sold to produce saleable meat of choice or select quality grade. Castration of male cattle is a common procedure that is practiced world-wide, but is more common in the U.S. than in many countries. Behavioral benefits from castration include reduced aggressiveness and sexual activity by reducing testosterone levels. In addition, castrated animals maintain a lower muscle pH post-harvest producing fewer “dark cutters.” Bulls have greater feeding performance and efficiency than steers. However, a bull’s ability to gain efficiently and produce a leaner carcass, with more value to the packer and retailer, is overshadowed by the perception that meat from bulls is less tender than meat from steers. Castration methods and the age at castration influence the potential stress on the animal, resulting in concerns regarding animal welfare and animal performance; therefore, castration of post-pubertal bulls to improve meat quality should be re-evaluated. The objective of this study was to evaluate the effects of castration and the use of growth promotion technologies in post-pubertal bulls on feeding performance, carcass traits, and meat quality characteristics compared to intact post-pubertal bulls.
Keywords: bulls; carcass; meat quality